Enhancement of network life-time for Power Efficient Gathering in Sensor Information System (PEGASIS) routing protocol in WSN - Hussaini, Muktar (Kulliyyah of Engineering,International Islamic University Malaysia, 2012)
Wireless Sensor Network (WSN) is a new and fast advancing technology, which is opening up many opportunities in the field of remote sensing and data monitoring. In spite of the numerous applications of WSN, issues related to designing a suitable and efficient routing protocol that will prolong the lifetime of the sensor network, and ensure safe delivery of data, have instead limited the performance of the WSN due to its diverse application scenario. A number of routing protocols have been proposed to address these challenges. However, the redundant data transmission, delay in time for data transmission and unnecessary increase in overheads make them inefficient and often lead to mismanagement of scarce energy and computational resources. This research addresses these challenges, by proposing a novel routing protocol which utilizes the energy aware greedy routing algorithm (EAGR), that adapts to the frequent changes in the distance of sensor nodes and energy level in forming a chain. Furthermore, the election of head node is made with the criteria of having higher residual energy and shortest distance to the base station, that relay data to the base station, to ensure that the proposed routing protocol is reliable enough to prolongs the network life time. The performance of the proposed routing protocol was evaluated using OMNET ++ and the results obtained were benclnliarked against Power-Efficient Gathering in Sensor Information Systems (PEGASIS). The simulation shows that the performance of the proposed enhanced PEGASIS developed in this research is more efficient when compared to original PEGASIS routing protocol. Enhanced-PEGASIS shows an improvement of 100 - 270% over PEGASIS in terms of network lifetime.